a 2 b 2 + c 2 ( a 2 + b 2 ) a 4 + b 4 + c 4
Find the value of the expression above if a + b + c = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
c o r r e c t ! @Vaibhav Prasad
( a + b + c ) 2 = a 2 + b 2 + c 2 + 2 ( a b + a c + b c ) = 0 ⇒ ( a 2 + b 2 + c 2 ) 2 = 4 ( a b + a c + b c ) 2 a 4 + b 4 + c 4 + 2 ( a 2 b 2 + b 2 c 2 + a 2 c 2 ) = 4 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) + 8 a b c ( a + b + c ) From a+b+c = 0: a 4 + b 4 + c 4 = 2 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) ∴ a 2 b 2 + c 2 ( a 2 + b 2 ) a 4 + b 4 + c 4 = ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) 2 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) = 2
(a^4+b^4+c^4)= (a^2+b^2+c^2)^2 - 2(a^2b^2+b^2c^2+c^2a^2) use this relation.
Can you elaborate more?
Problem Loading...
Note Loading...
Set Loading...
First simplify the denominator:
a 2 b 2 + c 2 ( a 2 + b 2 ) = a 2 b 2 + a 2 c 2 + b 2 c 2 = ( a b + a c + b c ) 2 − 2 a b c ( a + b + c ) But a + b + c = 0 .So 2 a b c ( a + b + c ) = 2 a b c ( 0 ) = 0 and we are left with ( a b + a c + b c ) 2 Now the numerator:
a 4 + b 4 + c 4 can be written as ( a 2 + b 2 + c 2 ) 2 − 2 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) .
Which can be written as ( ( a + b + c ) 2 − 2 ( a b + a c + b c ) ) 2 − 2 ( a 2 b 2 + a 2 c 2 + b 2 c 2 )
But we know that a 2 b 2 + a 2 c 2 + b 2 c 2 = ( a b + a c + b c ) 2 and that a + b + c = 0
So the numerator can be nicely simplified as ( 0 2 − 2 ( a b + a c + b c ) ) 2 − 2 ( a b + a c + b c ) 2 = 4 ( a b + a c + b c ) 2 − 2 ( a b + a c + b c ) 2 = 2 ( a b + a c + b c ) 2
So a 2 b 2 + c 2 ( a 2 + b 2 ) a 4 + b 4 + c 4 = ( a b + a c + b c ) 2 2 ( a b + a c + b c ) 2 = 2